2014
DOI: 10.1016/j.ccell.2014.10.021
|View full text |Cite|
|
Sign up to set email alerts
|

A BCL6/BCOR/SIRT1 Complex Triggers Neurogenesis and Suppresses Medulloblastoma by Repressing Sonic Hedgehog Signaling

Abstract: Disrupted differentiation during development can lead to oncogenesis, but the underlying mechanisms remain poorly understood. Here we identify BCL6, a transcriptional repressor and lymphoma oncoprotein, as a pivotal factor required for neurogenesis and tumor suppression of medulloblastoma (MB). BCL6 is necessary for and capable of preventing the development of GNP-derived MB in mice, and can block the growth of human MB cells in vitro. BCL6 neurogenic and oncosuppressor effects rely on direct transcriptional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 67 publications
1
77
0
Order By: Relevance
“…Recent studies have shown that Bcl6 overexpression (Tiberi et al, 2014) or direct FGF injection reduces proliferation of medulloblastoma cells in which Shh is hyperactivated (Emmenegger et al, 2013), supporting the idea that enhancing differentiation effectively prevents medulloblastoma progression in vivo.…”
Section: Pals1 Loss Forces Cell Cycle Exit Despite Hyperactive Shh Simentioning
confidence: 85%
“…Recent studies have shown that Bcl6 overexpression (Tiberi et al, 2014) or direct FGF injection reduces proliferation of medulloblastoma cells in which Shh is hyperactivated (Emmenegger et al, 2013), supporting the idea that enhancing differentiation effectively prevents medulloblastoma progression in vivo.…”
Section: Pals1 Loss Forces Cell Cycle Exit Despite Hyperactive Shh Simentioning
confidence: 85%
“…Here, our study for the irst time showed that the Smoothened (Smo) agonist purmophamine increased the expression of Sirt1, the Smoothened (Smo) antagonist cyclopamine decreased the expression of Sirt1, and the Sirt1 inhibitor sirtinol decreased the expressions of Shh, Ptc-1, Smo, and Gli-1proteins. Tiberi et al reported that a Sirt1 complex inhibited the Shh signaling in normal and oncogenic neural development [31]. Kong and Yang et al show that Notch signaling tunes neural progenitor responses to Shh by regulating traf icking of the Shh receptor Patched1 and downstream effector Smoothened to primary cilia.…”
Section: Discussionmentioning
confidence: 99%
“…Tiberi et al [109] recently demonstrated that BCL6 represses GLI1 and GLI2, effectors of the SHH pathway, through recruitment of BCOR and SIRT1 deacetylase. Because the targets of the BCL6/BCOR/SIRT1 complex depend on the cellular context, further studies are necessary to clarify the significance of this mutation in EBVaGC.…”
Section: Molecular Abnormalities Demonstrated By ‘Omics' Studiesmentioning
confidence: 99%